Compartment Syndrome of the Flexor Compartment of the Arm Secondary to Pectoralis Major Tendon Rupture - M. A. Tranovich; J. B. Stirton; J. C. Maier; M. B. Tanios; J. E. Lea; N. A. Ebraheim; J. D. Miller (Case Reports in Orthopedics)
Case. Compartment syndrome following muscle rupture is a rare entity with few mentions in the literature. We present a case of pectoralis major rupture in a 38-year-old male that evolved into compartment syndrome of the anterior compartment of the arm. Rupture of the pectoralis is uncommon and most often occurs during weight lifting. Compartment syndrome secondary to this injury is extremely uncommon, with only one reported case in the pectoralis major itself and several cases of biceps compartment syndrome. Due to the potentially devastating consequences of a missed compartment syndrome, it is imperative that physicians maintain a high level of suspicion in patients with these unusual injuries presenting with severe swelling and pain.